Answer:
First problem: [tex]y(x)=\frac{1}{2}+e^x-\frac{1}{2}e^{2x}[/tex]
Step-by-step explanation:
Solve for Y(s) by taking the transform of every term
[tex]y''-3y'+2y=1,\:y(0)=1,\:y'(0)=0\\\\\mathcal{L}\{y''\}-3\mathcal{L}\{y'\}+2\mathcal{L}\{y\}=\mathcal{L}\{1\}\\\\s^2Y(s)-sy(0)-y'(0)-3[sY(s)-y(0)]+2Y(s)=\frac{1}{s}\\\\s^2Y(s)-s-3[sY(s)-1]+2Y(s)=\frac{1}{s}\\\\s^2Y(s)-s-3sY(s)+3+2Y(s)=\frac{1}{s}\\\\(s^2-3s+2)Y(s)-s+3=\frac{1}{s}\\\\(s-1)(s-2)Y(s)=\frac{1}{s}-3+s\\\\Y(s)=\frac{1}{s(s-1)(s-2)}-\frac{3+s}{(s-1)(s-2)}[/tex]
Perform partial fraction decomposition
[tex]Y(s)=\frac{1-3s+s^2}{s(s-1)(s-2)}\\\\Y(s)=\frac{s^2-3s+1}{s(s-1)(s-2)}\\ \\\frac{s^2-3s+1}{s(s-1)(s-2)}=\frac{A}{s}+\frac{B}{s-1}+\frac{C}{s-2}\\\\s^2-3s+1=A(s-1)(s-2)+B(s)(s-2)+C(s)(s-1)[/tex]
Solve for each constant
[tex]s^2-3s+1=A(s-1)(s-2)+B(s)(s-2)+C(s)(s-1)\\\\(2)^2-3(2)+1=A(2-1)(2-2)+B(2)(2-2)+C(2)(2-1)\\\\-1=2C\\\\-\frac{1}{2}=C[/tex]
[tex]s^2-3s+1=A(s-1)(s-2)+B(s)(s-2)+C(s)(s-1)\\\\(1)^2-3(1)+1=A(1-1)(1-2)+B(1)(1-2)+C(1)(1-1)\\\\-1=-B\\\\1=B[/tex]
[tex]s^2-3s+1=A(s-1)(s-2)+B(s)(s-2)+C(s)(s-1)\\\\(0)^2-3(0)+1=A(0-1)(0-2)+B(0)(0-2)+C(0)(0-1)\\\\1=2A\\\\\frac{1}{2}=A[/tex]
Take the inverse transform to solve the IVP
[tex]Y(s)=\frac{\frac{1}{2}}{s}+\frac{1}{s-1}+\frac{-\frac{1}{2}}{s-2}\\ \\y(x)=\frac{1}{2}+e^x-\frac{1}{2}e^{2x}[/tex]